Comunicación Interna de los Departamentos Administrativo, Financiero y Jurídico del MIES Babahoyo - Vera Pincay, Danna Marina (2018)
Communication in the business world has become an essential factor for the execution of each of the processes that are carried out within the work activity being a tool among the members of the company that allows to develop and strengthen the relationships between the departments, the work environment and the commitment in the activities creating an integrating work climate.